2021
DOI: 10.1002/ps.6563
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fluazaindolizine on free‐living nematodes and the nematode community structure in a root‐knot nematode infested vegetable production system

Abstract: BACKGROUND Fluazaindolizine is a novel sulfonamide nematicide that is currently under commercialization in various countries. Four trials (two in tomato, two in zucchini) were carried out over two growing seasons in a root‐knot nematode (RKN; Meloidogyne incognita)‐infested plastic house to test the effects of a single application of fluazaindolizine at 1000 and 2000 g ha–1, on RKN, the resident nematode community and to estimate any side effects on the soil food web and soil ecological functions. The composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Many field studies have demonstrated the efficacy of fluazaindolizine against RKN on a series of crops including carrots, cucumber, tomato, and squash ( Becker et al ., 2019 ; Desaeger and Watson, 2019 ; Hajihassani et al ., 2019 ; Talavera et al ., 2021 ; Zhang et al ., 2021 ). However, to our knowledge, the efficacy of fluazaindolizine against RKN on sweet potato had not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many field studies have demonstrated the efficacy of fluazaindolizine against RKN on a series of crops including carrots, cucumber, tomato, and squash ( Becker et al ., 2019 ; Desaeger and Watson, 2019 ; Hajihassani et al ., 2019 ; Talavera et al ., 2021 ; Zhang et al ., 2021 ). However, to our knowledge, the efficacy of fluazaindolizine against RKN on sweet potato had not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Fluazaindolizine, oxamyl, and fluopyram all negatively impacted free-living nematodes, but only in 1 of 3 yr of the study (2020). A lab study showed that sensitivity to fluazaindolizine differed by free-living nematode species and the fitness of some species of bacteria-feeding species were negatively impacted ( Talavera et al ., 2021 ), but in general, free-living nematode fitness were not adversely impacted ( Thoden and Wiles, 2019 ; Talavera et al ., 2021 ). Our results are generally in line with these findings, and greater sensitivity of free-living nematodes to fluazaindolizine in 2020 could be a result of a greater proportion of bacterivores at the site in 2020, since this trophic group is more sensitive to fluazaindolizine ( Talavera et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Although synthetic non-fumigant nematicides have shown considerable efficacy in glasshouse and field trials, [20][21][22][23][24] not all plantparasitic nematodes share the same level of sensitivity to these compounds. 20,[25][26][27] For instance, in vitro exposure to fluazaindolizine for 72 h was more lethal to M. incognita and Tylenchulus semipenetrans (Cobb) than to Pratylenchus brachyurus (Godfrey) or Heterodera schachtii (Schmidt). 28 In vitro incubation studies with fluensulfone have shown similar results, with Aphelenchoides besseyi (Christie), A. fragariae (Ritzema Bos), Bursaphelenchus xylophilus (Steiner and Buhrer) and Ditylenchus dipsaci (Kühn) showing tolerance to fluensulfone exposure, whereas Pratylenchus penetrans (Cobb) and Xiphinema index (Thorne) were immobilized by this compound.…”
Section: Introductionmentioning
confidence: 99%
“…oxamyl), having greater specificity to targeted organisms as well as reduced risk to environmental and human health. 13 Although synthetic non-fumigant nematicides have shown considerable efficacy in glasshouse and field trials, [20][21][22][23][24] not all plantparasitic nematodes share the same level of sensitivity to these compounds. 20,[25][26][27] For instance, in vitro exposure to fluazaindolizine for 72 h was more lethal to M. incognita and Tylenchulus semipenetrans (Cobb) than to Pratylenchus brachyurus (Godfrey) or Heterodera schachtii (Schmidt).…”
Section: Introductionmentioning
confidence: 99%